2018
DOI: 10.3390/geriatrics3020028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religion, Spirituality and/or Belief in Positive Ageing for Older Adults

Abstract: (1) Background: The concept of positive ageing is gaining recognition as an approach to better understand the lives of older adults throughout the world. Positive ageing encompasses the various ways in which older adults approach life challenges associated with ageing and how certain approaches allow older adults to age in a more positive way. This paper makes a contribution to the field by examining the role of religion, spirituality and/or belief in relation to positive ageing; (2) Methods: Qualitative focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 50 publications
6
68
0
2
Order By: Relevance
“…Similar to the positive influence on psychological wellbeing identified in research on offline spiritual activities among Israeli Jews (Levin, 2013), it was evident that online religious counseling can be an important and empowering practice in later life, leading to spiritual growth, intellectual development and social connectedness. As Litwin and colleagues (2017) found, this spiritual involvement may be particularly significant for individuals with age-related mobility constraints, as it keeps them connected with community and spiritual life, providing them with a sense of empowerment, stability, support and direction and improving their emotional wellbeing during critical times (Malone & Dadswell, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the positive influence on psychological wellbeing identified in research on offline spiritual activities among Israeli Jews (Levin, 2013), it was evident that online religious counseling can be an important and empowering practice in later life, leading to spiritual growth, intellectual development and social connectedness. As Litwin and colleagues (2017) found, this spiritual involvement may be particularly significant for individuals with age-related mobility constraints, as it keeps them connected with community and spiritual life, providing them with a sense of empowerment, stability, support and direction and improving their emotional wellbeing during critical times (Malone & Dadswell, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the approach that does not separate spirituality from religiosity, spiritual wellbeing was defined as a satisfactory relationship with a transcendent deity and contact with one's inner being, as well as interaction and association with the religious community and environment (Fisher, 2011). Many studies have shown the importance of religion for spiritual wellbeing, especially in later life (e.g., Lifshitz et al, 2019;Malone & Dadswell, 2018;Shaw et al, 2016). Towards the end of their lives, people undertake religious involvement in the pursuit of physical healing, comfort and strength (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research about older people point to the health benefits of spirituality and religion. Spirituality can be a framework in daily living and a resource that supports positive ageing, and strengthen bodily and mental well-being and peacefulness, especially when older peoples' health deteriorates (Candy et al 2012;Ennis and Kazer 2013;Lavretsky 2010;Malone and Dadswell 2018;Toivonen et al 2018;Wallace and O'Shea 2007;Whitehead 2018;Zimmer et al 2016). Lavretsky (2010) claims that older people with a religious life view can find greater well-being than nonreligious people, as religious affiliation supports social relationships; moreover, religion can provide the answer to universal questions related to loss and death, as well as contribute to the maintenance of meaning in life.…”
Section: Research About Spirituality and Spiritual Care In Old Agementioning
confidence: 99%
“…The concept of spirituality is extremely general and multidimensional [7,10,11] anchored in subjective reasons and influenced by each person's life experiences, and includes a set of beliefs, that are not associated with religious doctrines [4] in order to disclose a meaning and understanding life search and trust in a transcendent source, in nature or others, with God or a higher power [7,8]. In religious people, spirituality may reflect the religious doctrine, creeds and philosophical beliefs being the life and disease understands in those perspective [12,13].…”
Section: Introductionmentioning
confidence: 99%